NARRATIVE REVIEW: COST-EFFECTIVENESS ANALYSIS OF THE USE OF ORAL ANTIDIABETIC DRUGS BIGUANIDE AND SULFONYLUREA GROUP IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Kezia Ivana; Dhigna Luthfiyani Citra Pradana; Citra Ayu Aprilia (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2022)
Diabetes Mellitus requires long-term management at a considerable cost. Therefore, a cost-Effectiveness analysis was used to assess several health interventions. Biguanide and Sulfonylurea provided the best results at the cheapest cost in this study. This study aims to gain a supporting theoretical foundation regarding the cost-effectiveness of using oral antidiabetic drugs biguanide and sulfonylureas in patients with type 2 diabetes mellitus. The method used in this study is a Narrative Review using literature that discusses the cost-effectiveness of oral antidiabetic drugs biguanide and sulfonylureas in patients with type 2 diabetes mellitus. Based on the results of this study, the age range of the occurrence of Type 2 Diabetes Mellitus is 45-65 years, with more percentage of male patients than women and a common complication is hypertension. In this study, the use of the biguanide drug (Metformin) was shown to provide a significant reduction in blood sugar levels at a reasonably low cost. The ICER results showed that combination drugs increased additional costs, but their use was more effective in healing and improving patients' quality of life. In conclusion to this study, the use of biguanide and sulfonylurea groups proved cost-effective compared to other antidiabetic drugs.